Comparative Effects of α-, β-, and γ-Carbolines on Platelet Aggregation and Lipid Membranes - Hironori Tsuchiya (Journal of Toxicology)
Cigarette smoking and alcohol consumption possibly affect platelet functions. To verify the hypothesis that some α-, β-, and γ-carboline components in cigarette smoke and alcoholic beverages may change platelet aggregability, their effects on human platelets were determined by aggregometry together with investigating their membrane effects by turbidimetry. Carbolines inhibited platelet aggregation induced by five agents with the potency being 3-amino-1,4-dimethyl-5H-pyrido[4,3-b]indole > 3-amino-1-methyl-5H-pyrido[4,3-b]indole > 1-methyl-9H-pyrido[3,4-b]indole. The most potent 3-amino-1,4-dimethyl-5H-pyrido[4,3-b]indole showed 50% aggregation-inhibitory concentrations of 6–172 μM. Both γ-carbolines interacted with phosphatidylcholine membranes to lower the lipid phase transition temperature with the potency correlating to the antiplatelet activity, suggesting that the interaction with platelet membranes to increase their fluidity underlies antiplatelet effects. Given their possible concentration and accumulation in platelets, γ- and β-carbolines would provide cigarette smokers and alcohol drinkers with reduced platelet aggregability, and they may be responsible for the occurrence of hemorrhagic diseases associated with heavy smoking and alcoholics.